Conocimientos del autoexamen mamario en estudiantes de la carrera de Medicina, Universidad Nacional de Loja - Quinde Quizhpe, Richard Fernando (2022)
Introduction: Breast cancer is the most frequent cancer in women worldwide, only in the Region of the America, 92,000 women died from this cause in 2017. However, in men it is a rare disease, its inciand has increased in the last 25 years. Breast self-examination constitutes a considerably significant preventive method as it allows for discovering a high percentage of breast lesions, hastening the diagnosis of those malignant lesions. This practice helps women and men to become familiar with the shape, size and texture of their breasts. When the routine of this technique is acquired, they become familiar with the characteristics of their breasts and the constant practice of breast self-examination is beneficial. Objectives: to determine the knowledge about breast self- examination among students of Human Medicine, Universidad Nacional de Loja. Methodology: a quantitative, descriptive study was carried out. The universe consisted of 274 students of the Universidad Nacional de Loja's Human Medicine career in a period of October-April 2021. The Blossiers 2014 questionnaire was applied, the data were and analyzed using Excel and SPSS and presented in tables and graphs. Results: it can be visualized that 22.9% obtained a rating of excellent, 8.7% outstanding, 21.9% very good, 30.6% good, 21.7% regular and 2.9% insufficient. Conclusions: The study population showed an elevated level of knowledge of breast self- examination, it was demonstrated that the higher the level of academic cycle, the higher the level of knowledge, and sex does influence the knowledge of breast self-examination.